Employment law - Ross, Jenifer (Law essentials., 2010)
Your introductory guide to the laws that govern and protect companies and workers in Scotland. From contracts to parental rights, and from unfair dismissal to discrimination, this guide explains employment law as it applies to employers, employees and lawyers in Scotland.